The Influence of Brand Experience and Brand Trust on Brand Loyalty at Esspecto Cafe Tondano - Nicole Natasya Ruth Kojongian; W. J. F. A. Tumbuan; Merinda H. C. Pandowo (Universitas Sam Ratulangi, 2022)
A cafe or coffee shop business is one of the most popular businesses in the city of Tondano. This is marked by the proliferation of coffee shops in all corners of the city of Tondano. The number of coffee shops that have sprung up has resulted in business owners trying to win the competition. Therefore, coffee shop entrepreneurs are required to have creativity in creating beverage flavored products that are sold, so that they differentiate from other beverage products that are sold by other coffee shops and can survive the competition. In carrying out business activities in order to survive, it is important to pay attention to customer orientation, which concerns what the company must do to find its customers. The objectives of this study are to Knowthe Effect of Brand Experience and Brand Trust on Brand Loyalty at Esspecto Coffee Shop Tondano. The analytical method used is multiple linear regression. Based on tTheresults of the hypothesis test found that simultaneously brand experience and brand trust had a significant effect on brand loyality at esspect, but partially brand experience has no significant effect on brand loyality at esspecto. For EsspectoCoffee to maintain and improve the quality of brand experience again so that it will make its consumers more loyal to the brand also satisfied and make them more comfortable being at Esspecto Coffee